Penerapan model pembelajaran kooperatif Tipe jigsaw untuk meningkatkan hasil belajar ipa siswa kelas v sdn 015 Bagan jawa bagansiapiapi - Sabariah '; Damanhuri Daud Damanhuri Daud; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The study was conducted in 015 Elementary School fifth grade Jawa Bagan Bagansiapiapi school year 2013-2014 in the second semester, which is held on 07 April to 21 April 2014, the number of students as many as 26 people. The background of this study is the low student science learning outcomes. The shape of this research is research done had classes (CAR) conducted as many as two cycles using data collection techniques such as observation sheets and daily test students. parameters measured include student learning outcomes, student mastery learning, appreciation group, the activity of the teacher, and student activities. From the results of the study showed an increase in students' science learning outcomes in Cycle I with an average of (66.15) and both categories in Cycle II (83.65) categories. Percentage of students' mastery learning Cycle I (57.69%) and incomplete in Cycle II (88.46%) did not complete. Activity Cycle I teachers (89%) either category, an increase in Cycle II (93%) excellent category. Student learning activities in Cycle I (69%) and enough categories Cycle II (91%) either category at all. From the above results it can be concluded that the application of the Jigsaw cooperative learning can improve learning outcomes IPA Elementary School fifth grade students. Jawa Bagan 015 Bagansiapiapi Academic Year 2013-2014. Keywords : Cooperative Learning Model Jigsaw, Learning Outcomes